Comparative analysis of the polarization and morphological characteristics of electrochemically produced powder forms of the intermediate metals - Nebojsa D. Nikolic; Predrag M. Zivkovic; Bojan Jokic; Miomir G. Pavlovic; Jasmina S. Stevanovic (Macedonian Journal of Chemistry and Chemical Engineering, 2014)
The polarization and morphological characteristics of powder forms of the group of the intermediate metals were examined by the analysis of silver and copper electrodeposition processes at high overpotentials. The pine-like dendrites constructed from the corncob-like forms, very similar to each others, were obtained by electrodeposition of these metals at the overpotential belonging to the plateaus of the limiting diffusion current density. The completely different situation was observed by electrodeposition of silver and copper at the overpotential outside the plateaus of the limiting diffusion current density in the zone of the fast increase of the current density with the overpotential. The silver dendrites, very similar to silver and copper dendrites obtained inside the plateaus of the limiting diffusion current density, were obtained at the overpotential outside the plateau. Due to the lower overpotential for hydrogen evolution for copper, hydrogen produced during copper electrodeposition process strongly affected the surface morphology of copper. The same shape of the polarization curves with the completely different surface morphology of Cu and Ag electrodeposited at overpotentials after the inflection point clearly indicates on the importance of morphological analysis in the investigation of polarization characteristics of the electrodeposition systems. Role of hydrogen as crucial parameter in the continuous change of copper surface morphology from dendrites to the honeycomb-like structures was investigated in detail. On the basis of this analysis, the transitional character of the intermediate metals between the normal and inert metals was considered. The typical powder forms characterizing electrodeposition of the intermediate metals were also defined and systematized.